Optical Glass
Patent Information
- Application Number
- JP2021124986
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-30
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-07-30
Smart Images

Figure 0007652653000003 
Figure 0007652653000004 
Figure 0007652653000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical glass, and more particularly to an optical glass having radiation resistance and showing little decrease in light transmittance in the visible range even when exposed to radiation such as gamma rays and X-rays. [Background technology]
[0002] In recent years, there has been an increasing demand for cameras, sensors, and the like to be used in spaces with high radiation exposure, such as outer space and inside nuclear facilities. Optical glass is used in these cameras and sensors. However, when conventional optical glass is exposed to radiation, its light transmittance in the visible range decreases and it becomes colored. Therefore, cameras and sensors using conventional optical glass can only function for a short period of time in spaces with high radiation exposure.
[0003] Patent Document 1 discloses glass for medical containers that is inhibited from coloring even when sterilized by radiation exposure. However, even before radiation exposure, the glass does not have the visible light transmittance required for optical glass. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-55092 A Summary of the Invention [Problem to be solved by the invention]
[0005] The problem to be solved by the present invention is to obtain an optical glass that has a visible light transmittance required for optical glass and that shows little decrease in visible light transmittance even when irradiated with radiation. [Means for solving the problem]
[0006] As a result of intensive research and testing, the present inventors have found that a glass that solves the above-mentioned problems can be obtained by having a specific composition and using specific physical properties as indicators, and have thus completed the present invention. Specifically, the present invention provides the following.
[0007] (1) Mass percent based on oxides: B2O3 content: 10.0-40.0% La2O3 component 15.0~55.0%, SiO2 content: 0-10.0%, ZnO content: 0 to 5.0% Y2O3 content: 0 to 20.0%, ZrO2 content: 0 to 5.0% Sb2O3 content: 0.05 to 1.0% CeO2 content: 0.1-3.0% Ln2O3 component is 20.0 to 70.0% (Ln is one or more selected from La, Gd, Y and Yb), Rn2O component is 0 to 10.0% (Rn is one or more selected from Li, Na, and K), Contains 0 to 20.0% MO components (wherein M is one or more selected from Mg, Ca, Sr, Ba, and Zn), The wavelength [λ80] at which the light transmittance of a 10 mm thick sample is 80% is 400 nm or more, When irradiated with cobalt-60 gamma rays at an absorbed dose of 0.2 kGy, the change in light transmittance at 450 nm [Δ450 nm] of a 10 mm thick sample is 20% or less.
[0008] (2) The optical glass according to (1), in which the wavelength [λ80] at which a sample having a thickness of 10 mm has a light transmittance of 80% is 490 nm or less.
[0009] (3) Refractive index [n d ] is 1.70000 or more and 1.80000 or less, and the Abbe number [ν d ] is 40.00 or more and 60.00 or less. Effect of the Invention
[0010] According to the present invention, it is possible to obtain optical glass that has a light transmittance in the visible range required for optical glass, and that, even when irradiated with radiation, shows little decrease in light transmittance in the visible range compared to before exposure to radiation. [Brief description of the drawings]
[0011] [Figure 1] 2 shows spectral transmittance curves of optical glasses according to Example 1 and Comparative Example 1. [Diagram 2] 2 is a spectral transmittance curve of the optical glass according to Example 4 before and after irradiation with cobalt-60 gamma rays. [Diagram 3] 3 is a spectral transmittance curve of the optical glass according to Comparative Example 2 before and after irradiation with cobalt-60 gamma rays. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The optical glass of the present invention will be described in detail below. In this specification, the content of each component is expressed in mass% based on the oxide. This is a method of expressing the composition of each component contained in the optical glass, assuming that the oxides, nitrates, etc., which are the raw materials of the optical glass of the present invention, are all decomposed and converted to oxides when melted.
[0013] The optical glass of the present invention contains, in mass % on an oxide basis, B2O3 content: 10.0-40.0% La2O3 component 15.0~55.0%, SiO2 content: 0-10.0%, ZnO content: 0 to 5.0% Y2O3 content: 0 to 20.0%, ZrO2 content: 0 to 5.0% Sb2O3 content: 0.05 to 1.0% CeO2 content: 0.1-3.0% Ln2O3 component is 20.0 to 70.0% (Ln is one or more selected from La, Gd, Y and Yb), Rn2O component is 0 to 10.0% (Rn is one or more selected from Li, Na, and K), Contains 0 to 20.0% MO components (wherein M is one or more selected from Mg, Ca, Sr, Ba, and Zn), The wavelength [λ80] at which the light transmittance of a 10 mm thick sample is 80% is 400 nm or more, An optical glass in which, when irradiated with cobalt-60 gamma rays to an absorbed dose of 0.2 kGy, the change in the light transmittance at 450 nm [Δ450 nm] of a 10 mm thick sample before and after irradiation is 20% or less. can be obtained.
[0014] The B2O3 component is an essential component that is indispensable as a glass-forming oxide. In particular, by containing 10.0% or more of the B2O3 component, the devitrification resistance of the glass can be improved and the dispersion of the glass can be reduced. Therefore, the lower limit of the content of the B2O3 component is preferably 10.0% or more, more preferably 11.0% or more, and most preferably 15.0% or more, and the upper limit of the content of the B2O3 component is preferably 40.0% or less, more preferably 38.0% or less, and most preferably 36.0% or less.
[0015] The La2O3 component increases the refractive index of the glass and reduces dispersion ( La2O3 is a component that increases the Abbe number. In particular, by containing 15.0% or more of the La2O3 component, a desired high refractive index can be obtained. Therefore, the lower limit of the content of the La2O3 component is preferably 15.0% or more, more preferably 20.0% or more, and most preferably 26.0% or more. On the other hand, by setting the content of the La2O3 component to 55.0% or less, the devitrification resistance of the glass can be improved. Therefore, the upper limit of the content of the La2O3 component is preferably 55.0% or less, more preferably 52.0% or less, and even more preferably 50.0% or less.
[0016] When the SiO2 content exceeds 0%, it increases the viscosity of the molten glass and reduces the coloring of the glass. It is an optional component that can reduce the glass composition and improve the devitrification resistance. Therefore, the lower limit of the content of the SiO2 component is preferably more than 0%, more preferably 1.0% or more, and most preferably 1.3% or more, and the upper limit of the content of the SiO2 component is preferably 10.0% or less, more preferably 8.0% or less, and most preferably 6.0% or less.
[0017] ZnO is an optional component that has the effect of lowering the liquidus temperature of glass and adjusting the optical constants to desired values. However, if the content of ZnO is too high, the devitrification resistance of the optical glass tends to deteriorate. Therefore, the upper limit of the ZnO content is preferably 5.0% or less, more preferably 4.0% or less, and most preferably 3.0% or less.
[0018] The Y2O3 component is an optional component that can reduce the material cost of the glass and the specific gravity while maintaining a high refractive index and a high Abbe number. Therefore, the lower limit of the content of the Y2O3 component is preferably more than 0%, more preferably 5.0% or more, and most preferably 7.0% or more. On the other hand, by making the content of the Y2O3 component 20.0% or less, the devitrification resistance of the glass can be improved. Therefore, the upper limit of the content of the Y2O3 component is preferably 20.0% or less, more preferably 18.0% or less, and most preferably 16.0% or less.
[0019] When the ZrO2 component is contained at more than 0%, it can contribute to a high refractive index and low dispersion of the glass, and can also improve the chemical durability of the glass. Therefore, the lower limit of the content of the ZrO2 component is preferably more than 0%, more preferably 1.0% or more, and most preferably 1.5% or more, and the upper limit of ZrO2 is preferably 5.0% or less, more preferably 4.0% or less, and most preferably 3.5% or less.
[0020] The Sb2O3 component promotes defoaming of the molten glass and has the effect of improving the transmittance in the short wavelength region in this glass system. The transmittance in the short wavelength region decreases due to the addition of CeO2, but this component has the effect of improving this. Therefore, the lower limit of the content of the Sb2O3 component is preferably 0.05% or more, more preferably 0.10% or more, and most preferably 0.15% or more, and the upper limit of the Sb2O3 component is preferably 1.0% or less, more preferably 0.9% or less, and most preferably 0.8% or less.
[0021] The CeO2 component has the effect of suppressing the decrease in the visible light transmittance of the optical glass caused by irradiation with radiation and preventing coloration. However, if the content is too high, the optical glass will be colored yellow. Therefore, the lower limit of the content of the CeO2 component is preferably 0.1% or more, more preferably 0.15% or more, and most preferably 0.2% or more, and the upper limit of the content of the CeO2 component is preferably 3.0% or less, more preferably 2.0% or less, and most preferably 1.7% or less.
[0022] The Ln2O3 component (Ln is one or more selected from La, Gd, Y and Yb) is 20.0%. The mass sum of the Ln2O3 component is preferably 20.0% or more, more preferably 25.0% or more, and most preferably 30.0% or more. On the other hand, the liquidus temperature of the glass is lowered by setting the mass sum to 70.0% or less, so that the devitrification resistance is improved. Therefore, the mass sum of the Ln2O3 component is preferably 70.0% or less, more preferably 65.0% or less, and most preferably 63.0% or less as the upper limit.
[0023] The Gd2O3 and Yb2O3 components are optional components that can increase the refractive index of the glass. However, the raw material prices of the Gd2O3 and Yb2O3 components are high, which is a factor in high costs, so it is preferable to limit the amount used. The upper limit of each component is preferably 10.0% or less, more preferably less than 8.0%, and even more preferably less than 5.0%.
[0024] The Rn2O component (Rn is one or more selected from Li, Na, and K) is an optional component that has the effect of promoting the melting of glass raw materials. However, if the content of the Rn2O component is too high, the chemical durability of the optical glass is likely to decrease. Therefore, the upper limit of the Rn2O component is preferably 10.0% or less, more preferably 8.0% or less, and most preferably 5.0% or less.
[0025] The Li2O component is an optional component that has the effect of promoting the melting of glass raw materials. However, if the content of the Li2O component is too high, the chemical durability of the optical glass is likely to decrease. Therefore, the upper limit of the Li2O component is preferably 3.0% or less, more preferably 2.0% or less, and most preferably 1.0% or less.
[0026] The Na2O component is an optional component that has the effect of promoting the melting of glass raw materials. However, if the content of the Na2O component is too high, the chemical durability of the optical glass is likely to decrease. Therefore, the upper limit of the Na2O component is preferably 5.0% or less, more preferably 4.0% or less, and most preferably 3.0% or less.
[0027] The K2O component is an optional component that has the effect of promoting the melting of glass raw materials. However, if the content of the K2O component is too high, the chemical durability of the optical glass is likely to decrease. Therefore, the upper limit of the K2O component is preferably 5.0% or less, more preferably 4.0% or less, and most preferably 3.0% or less.
[0028] The MO component (M is one or more selected from Mg, Ca, Sr, Ba, and Zn) is an optional component that has the effect of lowering the liquidus temperature of the glass and adjusting the optical constants to desired values. However, if the content of the MO component is too high, the devitrification resistance of the optical glass tends to deteriorate. Therefore, the upper limit of the MO component is preferably 20.0% or less, more preferably 18.0% or less, and most preferably 15.0% or less.
[0029] The MgO component is an optional component that has the effect of lowering the liquidus temperature of the glass and adjusting the optical constants to desired values. However, if the content of the MgO component is too high, the devitrification resistance of the optical glass tends to deteriorate. Therefore, the upper limit of the MgO component is preferably 5.0% or less, more preferably 4.0% or less, and most preferably 3.0% or less.
[0030] The CaO component is an optional component that has the effect of lowering the liquidus temperature of the glass and adjusting the optical constants to desired values. However, if the CaO content is too high, the devitrification resistance of the optical glass tends to deteriorate. Therefore, the upper limit of the CaO component is preferably 8.0% or less, more preferably 6.0% or less, and most preferably 4.0% or less.
[0031] The SrO component is an optional component that has the effect of lowering the liquidus temperature of the glass and adjusting the optical constants to desired values. However, if the content of the SrO component is too high, the devitrification resistance of the optical glass tends to deteriorate. Therefore, the upper limit of the SrO component is preferably 5.0% or less, more preferably 4.0% or less, and most preferably 3.0% or less.
[0032] The BaO component is an optional component that has the effect of lowering the liquidus temperature of the glass and adjusting the optical constants to desired values. However, if the content of the BaO component is too high, the devitrification resistance of the optical glass tends to deteriorate. Therefore, the upper limit of the BaO component is preferably less than 8.0%, more preferably 6.0% or less, and most preferably 4.0% or less.
[0033] Since the TiO2 component enhances the coloring caused by the CeO2 component and causes a decrease in light transmittance in the visible range, the upper limit of the TiO2 content is preferably less than 1%, more preferably 0.3% or less, and most preferably is substantially not contained.
[0034] Nb2O5 is a component that is useful for increasing the refractive index, but at the same time, it also increases dispersion. In order to achieve the target optical constants, the upper limit of the content is preferably less than 1.0%, more preferably 0.3% or less, and most preferably substantially none is contained.
[0035] WO3 is a component that is useful for increasing the refractive index, but at the same time, it also increases dispersion. In order to achieve the target optical constants, the upper limit of the content is preferably less than 1.0%, more preferably 0.3% or less, and most preferably substantially none.
[0036] Ta2O5 is a useful component for increasing the refractive index, but it is a very expensive raw material. In order to reduce the raw material cost, it is necessary to reduce the amount used, and the upper limit of its content is preferably less than 1.0%, more preferably 0.3% or less, and most preferably it is substantially not contained.
[0037] Even when added in small amounts, the transition metal components V, Cr, Mn, Fe, Co, Ni, Cu, and Mo will absorb light at specific wavelengths in the visible range, causing coloration. Therefore, in order to obtain the light transmittance required for optical glass, these components should not be substantially contained.
[0038] In the optical glass of the present invention, the wavelength [λ80] at which the light transmittance including reflection loss in a parallel plate sample having a thickness of 10 mm is 80% is preferably 400 nm or more, since even when irradiated with radiation, the decrease in light transmittance in the visible range is small compared to before exposure to radiation. More preferably, [λ80] is 400 nm or more, and most preferably, [λ80] is 405 nm or more. On the other hand, in order to ensure the visible light transmittance required of optical glass, the optical glass of the present invention preferably has [λ80] of 490 nm or less, more preferably 485 nm or less, and most preferably 480 nm or less.
[0039] In the optical glass of the present invention, the wavelength [λ5] at which the light transmittance including reflection loss becomes 5% in a parallel plate sample having a thickness of 10 mm is 425 nm or less and 350 nm or more. In a more preferred embodiment, [λ5] is 420 nm or less, and in the most preferred embodiment, [λ5] is 415 nm or less.
[0040] The optical glass of the present invention shows little decrease in light transmittance in the visible region even when irradiated with radiation. Thus, when the absorbed dose of cobalt-60 gamma rays is 0.2 kGy, the change in 450 nm light transmittance after exposure to gamma rays compared to the 450 nm light transmittance before exposure to gamma rays [Δ450 nm] is 20% or less. In a more preferred embodiment, Δ450 nm is 18% or less, and in the most preferred embodiment, [Δ450 nm] is 16% or less.
[0041] The optical glass of the present invention shows little decrease in light transmittance in the visible region even when irradiated with radiation. Thus, when the absorbed dose of cobalt-60 gamma rays is 0.2 kGy, the change [Δλ80] in [λ80] after exposure to gamma rays compared to [λ80] before exposure to gamma rays is 150 nm or less. In a more preferred embodiment, [Δλ80] is 100 nm or less, and in the most preferred embodiment, [Δλ80] is 80 nm or less.
[0042] The optical glass of the present invention shows little decrease in light transmittance in the visible region even when irradiated with radiation. Therefore, when the absorbed dose of cobalt 60 gamma rays is 0.2 kGy, the change [Δλ5] of [λ5] after exposure to gamma rays relative to [λ5] before exposure to gamma rays is 7 nm or less. In a more preferred embodiment, [Δλ5] is 6 nm or less, and in the most preferred embodiment, [Δλ5] is 5 nm or less.
[0043] The refractive index [n d The lower limit of the Abbe number [ν d ] has a lower limit of 40.00 or more and an upper limit of 60.00 or less. EXAMPLES
[0044] Examples and comparative examples of optical glass according to the present invention are shown below. The optical glass of the examples and comparative examples of the present invention was produced as follows. First, normal raw materials for optical glass, such as oxides, hydroxides, carbonates, and nitrates, were mixed to obtain the compositions of the examples and comparative examples shown in Table 1. Next, the mixed raw materials were placed in a platinum crucible and melted at 1100 to 1350°C for 2 to 5 hours depending on the melting property of the composition, and then the molten glass was homogenized by fining and stirring. Finally, the molten glass was cast into a stainless steel mold to be shaped, and then slowly cooled. Table 1 shows the present invention (Examples 1 to 6) and Comparative Examples 1 and 2.
[0045] The refractive index [n d ], Abbe number [ν d ], the spectral transmittance before exposure to radiation, and the spectral transmittance after exposure to radiation were measured. The refractive index (n d ) is measured using the V-block method specified in JIS B 7071-2:2018 for the d-line (587.56 nm) of a helium lamp. The Abbe number (ν d ) is the refractive index of the d line and the refractive index of the F line (486.13 nm) of a hydrogen lamp (n F ), and the refractive index for the C line (656.27 nm) (n C ) value, the Abbe number (ν d )=[(n d -1) / (n F -n C )] was calculated using the formula:
[0046] The spectral transmittance was measured in accordance with the Japan Optical Glass Industry Association standard JOGIS02-2003. Specifically, the spectral transmittance was obtained by measuring the transmittance of light with wavelengths of 200 to 800 nm for a 10±0.1 mm thick parallel polished product in accordance with JISZ8722. From the obtained spectral transmittance, the wavelength at which the light transmittance is 80% [λ80], the wavelength at which the light transmittance is 5% [λ5], and the transmittance at 450 nm [450 nm] were obtained. The produced optical glass was irradiated with radiation using a gamma ray irradiation facility for cobalt 60. Specifically, the optical glass was irradiated with cobalt 60 gamma rays so that the absorbed dose was 0.2 kGy.
[0047] The differences between the [λ80], [λ5] and [450nm] transmittance after exposure to gamma rays and the [λ80], [λ5] and [450nm] transmittance before exposure to gamma rays were calculated and designated as [Δλ80], [Δλ5] and [Δ450nm]. The measured [n d ], [ν d ], [λ80], [λ5], [450nm], [Δλ80], [Δλ5] and [Δ450nm] are shown in the table.
[0048] [Table 1]
[0049] [Table 2]
[0050] Fig. 1 shows the spectral transmittance curves of the optical glasses according to Example 1 and Comparative Example 1. The thickness of the sample is 10 mm. The solid line shows the spectral transmittance of Example 1, and the dashed line shows the spectral transmittance of Comparative Example 1. Comparative Example 1 is an example in which Sb2O3 is omitted from Example 1, and this figure shows that the present invention significantly improves the transmittance by adding a specified amount of Sb2O3.
[0051] Fig. 2 shows the spectral transmittance curves of the optical glass according to Example 4 before and after irradiation with cobalt-60 gamma rays, and Fig. 3 shows the spectral transmittance curves of the optical glass according to Comparative Example 2 before and after irradiation with cobalt-60 gamma rays. It was shown that in the composition not containing CeO2 such as Comparative Example 2, the transmittance was significantly reduced by irradiation with 60 gamma rays.
[0052] From the above examples, it can be seen that the optical glass of the present invention has a visible light transmittance required for optical glass, and even when irradiated with radiation, the visible light transmittance decreases little compared to before exposure to radiation. This makes it possible to use glass materials in the high refractive index, low dispersion region as lenses, and allows greater freedom in optical design for radiation-resistant glass.
Claims
1. In mass% based on oxide, B 2 O 3 Ingredients: 10.0-40.0%, La 2 O 3 Ingredients: 15.0-55.0%, SiO 2 Ingredients: 0-10.0%, ZnO content: 0 to 5.0% Y 2 O 3 Ingredients: 0-20.0%, ZrO 2 Ingredients: 0-5.0%, Sb 2 O 3 Components: 0.05 to 1.0%, CeO 2 Ingredients: 0.2-3.0%, Ln 2 O 3 component is 20.0 to 70.0% (Ln is one or more selected from La, Gd, Y and Yb), Rn 2 O component is 0 to 10.0% (Rn is one or more selected from Li, Na and K), Contains 0 to 20.0% MO component (wherein M is one or more selected from Mg, Ca, Sr, Ba, and Zn); The wavelength [λ80] at which the light transmittance of a sample having a thickness of 10 mm is 80% is 400 nm or more; An optical glass in which, when irradiated with cobalt-60 gamma rays to an absorbed dose of 0.2 kGy, the change in light transmittance at 450 nm [Δ450 nm] of a sample having a thickness of 10 mm before and after irradiation is 20% or less.
2. 2. The optical glass according to claim 1, wherein the wavelength [λ80] at which a sample having a thickness of 10 mm has a light transmittance of 80% is 490 nm or less.
3. Refractive index [n d ] is 1.70000 or more and 1.80000 or less, and the Abbe number [ν d 3. The optical glass according to claim 1, wherein the refractive index is 40.00 or more and 60.00 or less.
Citation Information
Patent Citations
Oxide fluorescent glass emitting visible fluorescence
JP1998167755A
Radiation shielding glass
JP1998226533A
Glass for medical container
JP2014055092A
Glass composition
WO2007077681A1